Simple Analytics of Productive Consumption - Suen, Wing; Mo, Pak Hung (Journal of Political Economy, 1994)
Productive consumption adds to utility and income at the same time. The shadow price of a productive good is equal to its money price less its marginal product. As more of the good is consumed, its shadow price rises because of diminishing productivity, and the consumer's full income also rises because the marginal product is positive. This paper uses a simple method to derive the comparative statics of the demand system when shadow prices and full income are endogenous. The direction of the overall bias induced by endogenous prices and income is found to be determinate. We demonstrate that the demand for productive goods tends to be relatively unresponsive to exogenous changes in prices and income. We also show that labor supply will be relatively unresponsive to wage and unearned income if market work causes fatigue.